2022
DOI: 10.1002/hsr2.933
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of suicide and suicide attempts in Jahrom district, Southern Iran in light of COVID pandemic: A prospective observational study

Abstract: Background and Aims Suicide is a global public health issue. The covid‐19 epidemic has led to disturbance in daily life and economic activity. It is assumed that increased stress and anxiety cause suicide. This study aimed to describe the causes and methods of committing suicide during the COVID pandemic. Methods This descriptive study was conducted on all outpatients, inpatients, and those who died during the period from March 21, 2021 to March 20, 2022 due to suicide attempts, referred to hospitals and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…The findings of this study showed that having a history of suicide increases the odds of death by 20 times [ 26 ]. Evidence shows that the history of suicide is one of the most important predictors of complete suicide [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study showed that having a history of suicide increases the odds of death by 20 times [ 26 ]. Evidence shows that the history of suicide is one of the most important predictors of complete suicide [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that the history of suicide is one of the most important predictors of complete suicide [ 27 , 28 ]. Therefore, to prevent further actions leading to suicide, these people should not be left alone after being discharged from the hospital and should be under the supervision of mental health support institutions to receive the necessary intervention measures [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Annually, more than 700 000 people die by suicide and there are more than 20 suicide attempts for each suicide. 3 Most suicides occur in low- and middle-income countries, 4 where early detection is difficult due to limited resources and services and inadequate treatment and support. 5 In Iran, the 20-year suicide mortality trend has increased with an estimated mean rate of 9.9 per 100 000 persons.…”
Section: Introductionmentioning
confidence: 99%